Medicine shortages in an Austrian community pharmacy: quantification and pharmacist intervention—a prospective observational study on shortage extent, patient support, and associated predictive factors - Alexander Schmidt-Ilsinger; Thomas Arzt; Petra Riegler; Trudi McIntosh (International Journal of Pharmacy Practice, 2026)
Abstract Background Medicine shortages increasingly challenge community pharmacies, affecting patient safety, increasing pharmacist workload, and straining healthcare systems. Little is known about shortages in Austrian community pharmacy settings. Aim To estimate the prevalence of medicine shortages in a community pharmacy in Austria, and describe how frequently pharmaceutical interventions were provided to mitigate their impact on patients. Methods This prospective, single-centre study was conducted over 8 weeks in an Austrian community pharmacy. Medicine shortages were identified using point-of-sale software during prescription dispensing. A structured data collection form was used to record patient demographics, affected medicines, and pharmaceutical interventions. Results Among 3182 patients, 212 (6.7%) experienced a shortage, involving 243 medicines (1.6%). Of these, 67.9% were permanent and 32.1% temporary shortages. Pharmacist-led interventions resolved 90.1% of cases. Intervention success rates were consistently high regardless of shortage duration. Conclusions Medicine shortages have become routine in Austrian community pharmacies. This study demonstrates the high acceptance and effectiveness of pharmacist-led interventions, irrespective of shortage duration. Findings support enhancing pharmacists’ role in medicine supply, including regulatory adjustments such as Aut-idem substitution.